Effects of cooling regime on the formation of voids in statically cooled waxy crude oil. (December 2015) - Chala, Girma T.; Sulaiman, Shaharin A.; Japper-Jaafar, Azuraien; Abdullah, Wan Ahmad Kamil Wan
Highlights: Effects of cooling regime on voids around pipe wall and core were investigated. Voids formed within gelled crude oil by 11.3% in volume via 3T-MRI system. Formation of voids potentially depends on different scenarios of cooling regime. Effects of cooling regime under constant start and end temperatures are presented. Abstract: Waxy crude oil solidifies when exposed to certain range of low seabed temperature. In this condition, predicting an accurate restart pressure in the pipeline has remained to be a challenge. Recent researches highlighted that the presence of gas voids in the gel has an impact on the gelled crude oil morphology and consequently on the restarting pressure. The gelling due to cooling of the oil is complex and not well understood. This study is aimed at analyzing the effects of cooling regimes on the formation of gas voids along and across the pipeline using a 3 T Magnetic Resonance Imaging (3 T-MRI) system. A flow loop rig simulating offshore oil transportation was designed and developed to produce the gel. It was found that voids were formed within gelled crude oil by 11.3% in volume. The results from the cooling regime under constant start temperature showed that the widest cooling regime resulted in a maximum voids volume in all regions in the pipe. However, reducing the cooling regime did not guarantee a decrease in volume of voids, for which lower cooling regimes occasionally resulted in a higher percentage of voids volume. For the cooling regimes under constant end temperature, in general, an increase in cooling regime resulted in a higher percentage of voids volume in the gel at lower end temperature. On the contrary, the intra-gel voids formation at higher end temperature was found to be different and a higher cooling regime did not result in a higher voids volume near pipe wall. Indeed, a higher cooling regime formed a higher percentage of voids volume around pipe core.